Performing Editorial Authority in Ingo Schulze’s Epistolary Novel Neue Leben - Anita Lukic (Studies in 20th & 21st Century Literature, 2018)
In this article, I argue that Ingo Schulze’s novel Neue Leben (New Lives, 2005) experiments with new forms of omniscient narration. Following the work of Paul Dawson, I show that the editor figure performs his authority as a public intellectual through the commentary he provides for the letters written by Enrico Türmer. The footnotes that the editor adds can be divided into two categories. In explanatory footnotes, the editor crosschecks Enrico’s references to the GDR against extra-fictional information that readers may find in newspapers, reference books, and other sources. By linking the fictional and extra-fictional discourse through his commentary, the editor becomes a public intellectual in Dawson’s sense. The critical footnotes problematize the editor’s role as a public intellectual, however, because they cite fictionalized documents and witness accounts. The editor runs up against a limit in his performance of narrative authority by referring to extra-fictional information, namely the fact that Enrico, as an individual, has said and done many things that left no documentary trace. The tension that the explanatory and critical footnotes produce in the figure of the editor is built into the epistolary novel, although Schulze exploits this tension to a far greater degree than anyone else. Schulze’s innovation within the epistolary novel is not purely formal, however. The explanatory and critical footnotes reveal the editor’s precarious status as he treads the line between private and public history.
Keywords: omniscient narration; omniscient narrator; omniscience; Wenderoman; epistolary novel; GDR; Schulze; Neue Leben; Dawson